Crushing behaviors of buckling-induced metallic meta-lattice structures - Jian-hua Dong; Yong-jun Wang; Feng-nian Jin; Hua-lin Fan (Defence Technology, 2022)
Thin-walled lattice materials can be applied as energy absorbers in protective structures of civil defense. In this paper, quasi-static in-plane crushing tests were carried out to investigate the crushing behavior and energy absorption of buckling induced meta-lattice structures (BIMSs) with different central angles made of plastic iron material DT3 and formed by wire cutting technique. Three crushing patterns were revealed and analyzed. The test results clearly show that the initial peak force (IPF), the crushing force efficiency (CFE), the specific energy absorption (SEA) and the mean crushing force (MCF) can be substantially improved by introducing buckling pattern into the straight-walled lattice structure. The MCF of the BIMS was consistently predicted based on the simplified super folding element (SSFE) and the flattening element.